CHILD-FRIENDLY SCHOOL IN REGIONAL PERSPECTIVE AND THE ROLE OF COUNSELING SERVICES - Afnibar Afnibar (STKIP Singkawang, 2017)
Globalization and free trade specifically in ASEAN countries clearly have impacts and changes in all aspects of life. One of the aspects of life is education. School is not only consist of Indonesian people, but also children from other countries because their parents study or work in Indonesia. Such conditions require a proper school for all children. The provision of infrastructure, educators and education personnel take effect in answering the challenge of such change. In the aspect of infrastructure needs to increase the number and the quality. Educators and education personnel must adjust to these changes. Educators at least are able to master the international language, minimal English. Child-friendly school is a school that provides comfort and happiness to all students, so that they develop optimally in accordance with the potential they have. The discussion in this paper comparatively sees the profiles of child-friendly school in Indonesia and ASEAN countries. It is expected the well defined of child-friendly schools in a regional perspective. The next thing will be analyzed is the association with the role of counseling in schools, as the process of giving the assistance so that learners become successful on academic, social relationships and career preparation.